2022
DOI: 10.1111/1748-8583.12465
|View full text |Cite
|
Sign up to set email alerts
|

Theorising the impact of macroturbulence on work and HRM: COVID‐19 and the abrupt shift to enforced homeworking

Abstract: This paper is among the first to fuse Social Exchange Theory (SET) with Boundary Theory (BT) to expand the knowledge of HR scholars and practitioners on the repercussions of macroturbulence for the management and experience of work. In‐depth interviews were conducted with 102 academics from UK universities to examine the nexus between COVID‐19 and changes to work at meso and micro levels. The findings extend SET and BT by elucidating how complex internal and external social exchange relationships interact more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
2
14
1
1
Order By: Relevance
“…This study focused on how employees in the London Insurance Market experienced and navigated their work identities during a period of significant macro-level changes in work practices (Hughes and Donnelly, 2022). The findings were examined through Goffman's theories to determine how participants perceived the impact of this global phenomenon on their professional selves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study focused on how employees in the London Insurance Market experienced and navigated their work identities during a period of significant macro-level changes in work practices (Hughes and Donnelly, 2022). The findings were examined through Goffman's theories to determine how participants perceived the impact of this global phenomenon on their professional selves.…”
Section: Resultsmentioning
confidence: 99%
“…, 2020; Carillo et al. , 2021; Hughes and Donnelly, 2022) to help recognise the critical importance of employees to contemporary organisations (Collings et al ., 2021a, b). This was achieved by placing a central focus on employees' perspectives to understand the evolving relationship between their work identities and the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On one side it is important to address this issue because of the digitization presenting fresh employee- and employer-level challenges, and on the other side, it is urgent as well because of the increased pace of digitization facilitated by macro-economic turbulence. As a result, scholars such as Hughes and Donnelly (2022) extended social exchange and boundary theories to accommodate homeworking as a consequence of the changed work–life boundaries. They observed that social exchange theory needs to be re-looked given the possibility of increased tensions between social exchange relationships and boundaries causing micro-level spillovers in case staff chooses to remain silent.…”
Section: Challenging the Status Quomentioning
confidence: 99%